Impact of a community-based diabetes self-management support program on adult self-care behaviors. Issue 1 (11th November 2022) - Dietz, C J; Sherrill, W W; Ankomah, S; Rennert, L; Parisi, M; Stancil, M
Abstract: Diabetes is a chronic condition that has reached epidemic proportions in the United States, affecting nearly 34 million adults, and disproportionately affecting vulnerable populations, such as ethnic minorities, the elderly and individuals with low socioeconomic status. This study addresses the impact of the Health Extension for Diabetes (HED) program, a community-based diabetes self-management support program, on adult diabetes self-care behaviors. The Summary of Diabetes Self-Care Activities (SDSCA) was utilized to evaluate improvement in diabetes self-care behaviors. Descriptive statistics, univariate and multivariable regression models were conducted. Significant increases were observed among program participants ( N = 149) in all five subscales of the SDSCA (general diet, specific diet, blood glucose testing, exercise and foot care; P -values < 0.001). A priority of this diabetes education program was helping underserved populations; over half (62%) of participants self-identified as Black/African Americans. After program participation, scores on all SDSCA subscales increased significantly among Black/African Americans ( n = 93) by approximately 1 day per week. White/other races ( n = 56) showed similar increases in four of the SDSCA subscales post-HED program participation. This study shows that increasing participation in community-based, diabetes self-management support programs, such as HED, can increase engagement in diabetes self-care behaviors among underserved groups.